INOVASI PEMBELAJARAN PENDIDIKAN KREATIF MENUJU PROFESIONALISME GURU - Fatmiyati, Fatmiyati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—Innovative learning needs to be implemented to answer the challenges of the 21st century. To produce innovative learning, all learning components which include teachers, students, teaching materials, achievement of competencies, and evaluation of learning need to be innovated. The application of innovative aspects is explained in several examples of innovative learning models; includes models of inquiry learning, contextual, thematic, creative-productive, and higher-order thinking. The point is that innovative science learning is learning that can equip the accompaniment effect of learning which includes higher-order thinking and generic Science skills. In implementing innovative learning professional teachers are needed. Professional teachers have competence is in accordance with the competency standard in National Education Minister Regulation no 16/2007 and RI no 74/2008.Keywords—innovative learning, generic science skills, teacher professionalism Abstrak—Pembelajaran inovatif perlu dilaksanakan untuk menjawab tantangan abad ke 21 ini. Untuk menghasilkan pembelajaran inovatif, semua komponen pembelajaran yang meliputi guru, siswa, bahan ajar, capaian kompetensi, dan evaluasi pembelajaran perlu diinovasi. Penerapan aspek-aspek inovatif dijelaskan dalam beberapa contoh model pembelajaran inovatif; meliputi model pembelajaran inkuiri, kontekstual, tematik, kreatif- produktif, dan berpikir tingkat tinggi. Intinya pembelajaran Sains inovatif merupakan pembelajaran yang dapat membekalkan efek iringan pembelajaran yang meliputi berpikir tingkat tinggi dan keterampilan generik Sains. Dalam pelaksanaan pembelajaran inovatif diperlukan guru yang profesional. Guru professional memiliki kompetensi sesuai dengan standard kompetensi dalam permendiknas no 16/2007 dan pp RI no 74/2008.Kata kunci— pembelajaran inovatif, keterampilan generik Sains, profesionalisme guru